Project-Based Learning in High School Mathematics (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
AbstractAs national math scores continue to decline, it is obvious that the methods we are using to teach math are not working.  There is an evident need to find instructional methods that make math relevant and worthwhile.  Project-based learning has received attention lately as an instructional technique that engages students in active learning.  Research supports that the use of project-based learning activities has a positive influence on student engagement.  Additionally, studies have found that students demonstrate a better, deeper understanding of the content through project-based learning activities.  By using project-based learning in a high school mathematics classroom, educators can enhance student engagement and motivation which have a direct impact on student achievement.            Keywords:  project-based learning, engagement, achievement